Dynamic Magnetic Resonance Imaging Demonstrates the Integrity of Perineal Reconstruction following Cylindrical Abdominoperineal Excision with Reconstruction of the Pelvic Floor Using Porcine Collagen. (22nd January 2012) - Kavanagh, D. O.; Imran, H.; Almoudaris, A.; Ziprin, P.; Faiz, O.
Abstract : A 72-year-old female presented with a six-month history of increased frequency of defecation, rectal bleeding, and severe rectal pain. Digital rectal examination and endoscopy revealed a low rectal lesion lying anteriorly. This was confirmed histologically as adenocarcinoma. Radiological staging was consistent with a T3 N2 rectal tumour. Following long-course chemoradiotherapy repeat staging did not identify any metastatic disease. She underwent a laparoscopic cylindrical abdominoperineal excision with en bloc resection of the coccyx and posterior wall of the vagina with a negative circumferential resection margin. The perineal defect was reconstructed with Permacol (biological implant, Covidien) mesh. She had no clinical evidence of a perineal hernia at serial followup. Dynamic MRI images of the pelvic floor obtained during valsalva at 10 months revealed an intact pelvic floor. A control case that had undergone a conventional abdominoperineal excision with primary perineal closure without clinical evidence of herniation was also imaged. This confirmed subclinical perineal herniation with significant downward migration of the bowel and bladder below the pubococcygeal line. We eagerly await further evidence supporting a role for dynamic MR imaging in assessing the integrity of a reconstructed pelvic floor following cylindrical abdominoperineal excision.